Defining a Fashion Industry Value Stream in a Small Island Developing State - Cilla Thadeen Benjamin (International Journal of Supply Chain Management, 2016)
The economies of the Small Island Developing States of the Caribbean have traditionally been based on low value adding activities within global value streams. This has occured even when there was knowledge and opportunity for industrial upgrading to occur. This study looks at the Fashion Industry of Trinidad and Tobago and investgates whether there exists opportunity for owning or occupying lead positions in global fashion industry value streams.